Lateral gene transfer and gene duplication played a key role in the evolution of Mastigamoeba balamuthi hydrogenosomes - Nývltová, Eva; Stairs, Courtney W; Hrdý, Ivan; Rídl, Jakub; Mach, Jan; Pačes, Jan; Roger, Andrew J; Tachezy, Jan (Molecular biology and evolution, 2015)
Lateral gene transfer (LGT) is an important mechanism of evolution for protists adapting to oxygen-poor environments. Specifically, modifications of energy metabolism in anaerobic forms of mitochondria (e.g., hydrogenosomes) are likely to have been associated with gene transfer from prokaryotes. An interesting question is whether the products of transferred genes were directly targeted into the ancestral organelle or initially operated in the cytosol and subsequently acquired organelle-targeting sequences. Here, we identified key enzymes of hydrogenosomal metabolism in the free-living anaerobic amoebozoan Mastigamoeba balamuthi and analyzed their cellular localizations, enzymatic activities, and evolutionary histories. Additionally, we characterized 1) several canonical mitochondrial components including respiratory complex II and the glycine cleavage system, 2) enzymes associated with anaerobic energy metabolism, including an unusual D-lactate dehydrogenase and acetyl CoA synthase, and 3) a sulfate activation pathway. Intriguingly, components of anaerobic energy metabolism are present in at least two gene copies. For each component, one copy possesses an mitochondrial targeting sequence (MTS), whereas the other lacks an MTS, yielding parallel cytosolic and hydrogenosomal extended glycolysis pathways. Experimentally, we confirmed that the organelle targeting of several proteins is fully dependent on the MTS. Phylogenetic analysis of all extended glycolysis components suggested that these components were acquired by LGT. We propose that the transformation from an ancestral organelle to a hydrogenosome in the M. balamuthi lineage involved the lateral acquisition of genes encoding extended glycolysis enzymes that initially operated in the cytosol and that established a parallel hydrogenosomal pathway after gene duplication and MTS acquisition.
Keywords: energetický metabolismus; duplikace genu; Cell Membrane Structures; přenos genů horizontální; acetylCoA synthetase; Enzymes; struktury buněčné membrány; anaerobióza; enzymy; molekulární evoluce; Evolution, Molecular; PFO; Gene Duplication; sulfate activation pathway; organely; glycine cleavage system; Gene Transfer, Horizontal; Organelles; Energy Metabolism; Archamoebae; Anaerobiosis; hydrogenase; succinate dehydrogenase